2014
DOI: 10.1093/humrep/det456
|View full text |Cite
|
Sign up to set email alerts
|

No evidence that embryo selection by near-infrared spectroscopy in addition to morphology is able to improve live birth rates: results from an individual patient data meta-analysis

Abstract: There is at present no evidence that NIR spectroscopy of spent embryo culture media in its current form can be used in daily practice to improve live birth rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 27 publications
0
23
1
1
Order By: Relevance
“…These results were then supported by another RCT, which also failed to show improvement of live birth rate after day 3 transfer when using NIR spectroscopy (Vergouw et al, 2012). Evaluations of this technical platform by some principal investigators suggested that the threshold of spectral signal used to predict viability was not strong enough and was highly sensitive to signal noise, impairing the robustness and reproducibility of the analysis and the performance of the predictive algorithms (Sakkas, 2014;Vergouw et al, 2014).…”
Section: Article In Pressmentioning
confidence: 93%
“…These results were then supported by another RCT, which also failed to show improvement of live birth rate after day 3 transfer when using NIR spectroscopy (Vergouw et al, 2012). Evaluations of this technical platform by some principal investigators suggested that the threshold of spectral signal used to predict viability was not strong enough and was highly sensitive to signal noise, impairing the robustness and reproducibility of the analysis and the performance of the predictive algorithms (Sakkas, 2014;Vergouw et al, 2014).…”
Section: Article In Pressmentioning
confidence: 93%
“…,b; Vergouw et al . ). However, NIR and Raman analysis are generally used for overall spectral profile comparison, and are primarily aimed at distinguishing viable from non‐viable embryos with regard to either developmental or pregnancy potential.…”
Section: Discussionmentioning
confidence: 97%
“…When dealing with the transfer of fresh embryos, extensive effort is being made towards improving our ability to select viable embryos out of a cohort of cleavage embryos or blastocysts (time lapse analysis, gene expression analysis, metabolomics, etc.) [8,40,41]. However, selection tools for the transfer of thawed embryos are still based on survival and morphology.…”
Section: Discussionmentioning
confidence: 99%